Feature Analysis of the “Customer Relationship Management” Systems for Higher Education Institutions - Hugo de Juan-Jordán; María Guijarro-García; Javier Hernandez Gadea (Multidisciplinary Journal for Education, Social and Technological Sciences)
Universities, business schools and other higher education institutions all over the world are experiencing deep changes in the way they work and interrelate with their ‘clients’, i.e. students and their relatives, alumni and donors, faculty and staff members, because these constituents are demanding more attention through different channels as well as immediate response and service. Technology - materialized in the form of Customer Relationship Management (CRM) systems - is the great promise for solving these demands. This article summarizes the features a CRM system should possess to make educational institutions thrive in the current digital era, and points out the future trends on this topic. The final objective is neither an analysis of the applications available on the market nor a selection guide, but a recommendation for the end users to utilize a CRM system when considering achieving some of the business needs implied in the features available on these CRMs.